Probiotics: Reality of benefits for life, a review - Okamoto, A. S. [UNESP]; Andreatti Filho, R. L. [UNESP] (My University, 2016)
The intestinal mucosa is constantly exposed to the action of pathogens, but these agents are not always able to cause damage. This is mainly because the bacteria of the normal intestinal microbiota present in this mucosa present several types of inhibitory antagonistic actions. These actions consist of mechanisms that pit beneficial bacteria against pathogenic bacteria, thereby highlighting the competition for binding sites in enterocytes. This consequently reduces the adhesion and penetration of other bacteria, increases the competition for nutrients in the same niche in which they live, stimulates the cellular and humoral immune system and produces various antibacterial substances. The normal intestinal flora consists of numerous species of microorganisms that, besides their protective function, favor development of the intestinal villi and their recovery after an event that damages them, thus ensuring better absorption of the nutrients available. Much research is being conducted in this field, especially with regard to the action of certain bacteria that promote the same function as the normal intestinal microflora. These bacteria are termed selective probiotics, and they are administered so as to provide health benefits for the host. As well as probiotics, organic acids and prebiotics have also been used in the diet, with the main purpose of modulating the normal intestinal microbiota. Use of these products in animal production has now become a reality, particularly with regard to replacing chemicals such as antibiotics. This has come about through pressure exerted by consumers in the most demanding markets, given the possibility of antimicrobial resistance and residues of chemicals in chicken meat and eggs. The use of these products in food and feed is increasing, based on proven satisfactory results, although full understanding of the mechanisms of action of these products is far from being achieved. Thus, many further studies will be needed, especially with regard to developing products that are more effective.
Keywords: Enteropathogenic bacteria; Intestinal colonization; Pathogens; Probiotics